A qualitative exploration of mentally tough behaviour in Australian football. Issue 3 (1st February 2020) - Anthony, David R.; Gordon, Sandy; Gucciardi, Daniel F.
ABSTRACT: The primary aim of this research was to generate insight into observable mentally tough behaviours, or MTb, across different contexts (e.g., training and competition) in an Australian football (AF) environment. A second aim of this research was to explore the utility of MTb as a distinct concept, and identify common behavioural qualities associated with MTb that separate it from other similar constructs. In total, 10 experienced full-time football operations staff were interviewed using a semi-structured interview guide, with inductive thematic analysis employed to analyse the data. Five main themes relating to MTb were identified: adaptive development, consistent training conduct, composed performance actions, responsible and accountable, and team supportive. Overall, the findings of the research provided preliminary support for the proposition that there exists a collection of MTb that are displayed more frequently by athletes considered to possess high levels of mental toughness compared to athletes who are perceived to have low levels of this psychological capacity. We propose a collection of necessary and sufficient behavioural qualities and a working definition of MTb to further our understanding of potential strategies to develop MT.